Effect of Estradiol Valerate on Endometrial Thickness in Infertile Polycystic Ovarian Syndrome Patients- A comparative Study in a Tertiary Level Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a complex heterogeneous endocrine disorder, occurring due to synergistic interaction of genetic, epigenetic and environmental factors, associated with both reproductive and metabolic abnormalities resulting in shortterm and long-term consequences on the women’s health. The incidence of anovulatory infertility in PCOS is 70% to 8 0% higher than who don’t have PCOS. With ovulation induction adequate endometrial development is needed for pregnancy to occur. Improper endometrial thickness i.e. < 7 mm are considered to be less able to sustain implantation and pregnancy.Objective: To study the effect of estradiol valerate on the endometrial thickness in PCOS cases receiving letrozole for induction of ovulation as compared to letrozole alone.Materials & Methods: This Quasi-experimental type of interventional study was conducted in the outpatient department (OPD) of reproductive endocrinology and infertility Unit, Dhaka Medical College Hospital (DMCH), Dhaka for 12 months from July 2021 to June 2022. The study included 65 infertile PCOS patients based on the Rotterdam criteria with improper endometrial thickness. Patients were divided into 2 groups: ovulation induction was given in group A by letrozole 5 mg from day 3 to day 7 of menstruation and 4 mg estradiol valerate from the 8th day of menstruation until 12th day and in group B by 5 mg letrozole from day 3 to day 7 of menstruation.Results: This study showed that endometrial thickness was increased in both groups. In Group A from 6.15±0.48 to 9.70±1.03 and in Group B from 6.29±0.46 to 7.52±0.59. But, Group A showed significantly higher endometrial thickness compared to Group B (p